The third harmonic generated voltage by salient-pole synchronous generator during 3-phase–to–ground fault - Shah Riman, N.I. (John Wiley and Sons Ltd, 2017)
Conducted experiment proves that third harmonic (TH) component of salient-pole synchronous generator behaves differently compared with fundamental frequency component in terms of generated voltage. Fundamental frequency-generated voltage depends on the excitation system, and the generated voltages before and during fault are almost the same. However, TH-generated voltage is independent of the excitation system. In other words, variation of the excitation current does not affect the generation of TH voltage as much as it affects the generation of fundamental frequency voltage. On top of that, the generation of TH voltage before and during fault varies significantly. Hence, a typical method to solve fault analysis for 3-phase–to–ground fault is not applicable in TH domain. Therefore, in this article, a method to find TH-generated voltage is proposed. The TH-generated voltage during 3-phase–to–ground fault is presented in terms of percentage called the harmonic fundamental ratio, which is the ratio of TH zero-sequence–generated voltage to fundamental frequency–positive sequence-generated voltage during fault. The harmonic fundamental ratio is obtained by short circuiting the generator terminal prior to the application in the system. It turns out that the generated TH voltage by synchronous generator depends on the zero-sequence TH impedance of the TH fault current path. Lastly, the proposed method to obtain TH-generated voltage by salient-pole synchronous generator is validated by comparing the calculated TH fault current with the actual TH fault current obtained from experiment. Copyright © 2017 John Wiley & Sons, Ltd.